2006
DOI: 10.1111/j.1365-2929.2005.02343.x
|View full text |Cite
|
Sign up to set email alerts
|

The risks and benefits of being a young female adolescent standardised patient

Abstract: Adolescent females showed no adverse effects when used extensively to portray risk-taking SPs. The focus groups provided the adolescents with an opportunity to debrief together. The adolescent SPs reported benefiting from this study but requested unanimously that they come "out of character" when giving feedback to the medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 17 publications
0
66
0
Order By: Relevance
“…Studies have reported on single experiments with adolescent SPs (Woodward & Gliva-McConvey 1995;Lane et al 1999;Hardoff & Schonmann 2001;Brown et al 2005) or on short term follow-up of adolescent SPs (Blake & Greaven 1999a, b;Hanson et al 2002;Blake et al 2006). However, we have found no studies in which an adolescent SP program was evaluated over multiple years.…”
Section: Practice Pointsmentioning
confidence: 80%
See 4 more Smart Citations
“…Studies have reported on single experiments with adolescent SPs (Woodward & Gliva-McConvey 1995;Lane et al 1999;Hardoff & Schonmann 2001;Brown et al 2005) or on short term follow-up of adolescent SPs (Blake & Greaven 1999a, b;Hanson et al 2002;Blake et al 2006). However, we have found no studies in which an adolescent SP program was evaluated over multiple years.…”
Section: Practice Pointsmentioning
confidence: 80%
“…The first focuses on the effects of role playing on the adolescent. Most studies found no negative effects of role playing on adolescent SPs (Woodward & GlivaMcConvey 1995;Blake & Greaven 1999a;Hanson et al 2002;Blake et al 2006). However, in a recent study adolescent SPs performing a suicidality role showed behavioral effects suggesting a transient depressive reaction (Hanson et al 2007).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations